Izzivi logopedske obravnave odraslih v času epidemije - Pirc, Špela (Rehabilitacija (Ljubljana), 2021)
During the last year, we have been facing changes in the field of speech and language therapy due to the epidemic of coronavirus disease. Because of the anti-corona safety measures and the reorganisation of work within the institution, it has become more difficult to for neurological outpatients to have access to treatment. The gap due to the absence of outpatient treatments was partially filled by the implementation of speech therapy in the form of telerehabilitation. Mandatory use of protective equipment affected the course and effectiveness of direct speech therapy. Here we present in more detail the individual challenges faced by speech and language therapists during the epidemic due to COVID-19 disease and related protective measures. We limited ourselves to the implementation of speech therapy in adult neurological patients and to three content areas that are most often the subject of speech therapy in these patients: hearing impairment, speech and language disorders and swallowing disorders.
Keywords: communication; coronavirus; COVID-19; dysphagia; hearing; komunikacija; koronavirus; logopedija; motnje požiranja; rehabilitation; sluh; speech and language therapy; Speech Disorders; telerehabilitacija; telerehabilitation